EGG QUALITY RESEARCH ON CONTAMINATION IN VARIOUS SEASONAL CONDITIONS - Artur GOLBAN; RitaGOLBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The scientific research reflected in this study aimed to identify the quality of chicken eggs regarding bacterial contamination in different seasonal conditions. The scientific researches were performed using the following research methods: microscopic visualization, qualitative and quantitative analysis, induction, deduction, the graphics method, the chronological series method. The results of the research highlighted the general prevalence of microbial germs on the eggshell surface during the autumn season, followed by the spring season and finally a lower prevalence during the winter season. Salmonella species were not identified. In the scientific research are analysed the egg production per region, revenue in the egg market of Moldova, sales channels of eggs and egg quality in different seasonal conditions. In the same time the research finishes with conclusions/recommendations related the egg quality assurance and bacterioscopic results.